Pemberantasan Rabies di Indonesia sebagai Upaya Mewujudkan Right to Life, Right to Health - Risqa Novita (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Rabies is one of infectious diseases from animals to man which gets serious attention from the government due to its high mortality in human.Until 2017, as many as 26 provinces in Indonesia has not been free from Rabies yet. The purposes of this writing are to uncover the influence of health law of the people in Indonesia on the implementation of rabies eradication in Indonesia. Beside, this could be used by the policy makers to unity programs to realize people’s right to life, right to health toward Indonesia being free from rabies in 2030. The current legislations are considered sufficient ,but not their implementations. The regulations are mostly made by the central government , while the local government are the implementor. Local regultaions, therefore, are needed as umbrella for the eradication program in the areas. To conclude, public health and other laws have influenced the eradication efforts of the disease. Public health law influences the implementation of eradication of rabies in Indonesia, and to realize right to life and right to health in bringing together various aspects that influence the eradication of rabies in Indonesia so that the goal of Indonesia to be free from rabies in 2030 can be achieved.